STRATEGI DIPLOMASI PERTAHANAN INDONESIA DALAM KERJA SAMA TRILATERAL COOPERATIVE ARRANGEMENT (PORT VISIT INDOMALPHI 2017-2019) - Chaer, Muh Idhan; Sumarlan, Sutrimo; Widodo, Pujo (Universitas Perrtahanan Indonesia (UNHAN), 2021)
The Sulu-Sulawesi Sea is a strategic trade route so that it becomes one of the policy priorities. Strategic value does not necessarily bring benefits, but also brings security threats such as piracy, piracy and kidnapping with a ransom demand. In an effort to overcome this, since 2017 the Trilateral Cooperative Arrangement in the Port Visit scheme has been built between the three countries of Indonesia, Malaysia, and the Philippines. The purpose of this study is to analyze the form of Port Visit cooperation and to analyze the Indonesian Defense Diplomacy Strategy in this cooperation. This research uses defense theory, strategy theory, and defense diplomacy theory. This study uses a qualitative descriptive analysis research method. The data collection carried out in this study used primary data through interviews and secondary data from a literature review of journals, books, reports, and internet-based sources. The Trilateral Port Visit Indomalphi cooperation is a response in dealing with transnational crimes in the Sulu-Sulawesi Sea area. With various series of activities, this cooperation plays an important role in efforts to maintain regional security and stability and provides the authority to maintain the safety of all Indonesian citizens as mandated by the law. The Indonesian Defense Diplomacy Strategy in the Indomalphi Port Visit is aimed at increasing mutual trust and military capacity in terms of coordination, communication and piracy capture training. Therefore, the defense diplomacy strategy in this study can be said to have fulfilled the two main characters of defense diplomacy, namely; defense diplomacy to build mutual trust (CBMs) and defense diplomacy to build defense capacity (CB).